2016
DOI: 10.1021/acs.jafc.6b01029
|View full text |Cite
|
Sign up to set email alerts
|

Validated UPLC-MS/MS Methods To Quantitate Free and Conjugated Alternaria Toxins in Commercially Available Tomato Products and Fruit and Vegetable Juices in Belgium

Abstract: Ultra-performance liquid chromatography tandem mass spectrometry and Quick, Easy, Cheap, Effective, Rugged and Safe based analytical methodologies to quantitate both free (alternariol (1), alternariol monomethyl ether (2), tenuazonic acid (3), tentoxin (4), altenuene (5), altertoxin-I (6)) and conjugated (sulfates and glucosides of 1 and 2) Alternaria toxins in fruit and vegetable juices and tomato products were developed and validated. Acceptable limits of quantitation (0.7-5.7 µg/kg), repeatability (RSD r < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
86
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(89 citation statements)
references
References 44 publications
3
86
0
Order By: Relevance
“…defining a mycotoxin derivative that may be cleaved during digestion in living organisms to release its parent form. However, these conjugated mycotoxins are currently known as "modified mycotoxins" after a more recent comprehensive classification [47]. It is not clear if these modified mycotoxins can be hydrolyzed and absorbed in the gastrointestinal tract, thereby further contributing to the overall exposure.…”
Section: Stability Of Alternaria Mycotoxins the Stability Ofmentioning
confidence: 99%
See 3 more Smart Citations
“…defining a mycotoxin derivative that may be cleaved during digestion in living organisms to release its parent form. However, these conjugated mycotoxins are currently known as "modified mycotoxins" after a more recent comprehensive classification [47]. It is not clear if these modified mycotoxins can be hydrolyzed and absorbed in the gastrointestinal tract, thereby further contributing to the overall exposure.…”
Section: Stability Of Alternaria Mycotoxins the Stability Ofmentioning
confidence: 99%
“…Alternaria toxins are, together with aflatoxins, ochratoxin A, and patulin, the most commonly found mycotoxins in fruits and their processed products. Due to the limitations of current industrial processes to completely eliminate the rotten tissues and the reported stability of some Alternaria mycotoxins (i.e., AOH, AME, and ATXs) in fruit juices and during tomato processing, it is obvious that these mycotoxins are likely to be present in commercial end products [47].…”
Section: Prevalence Of Alternaria Mycotoxinsmentioning
confidence: 99%
See 2 more Smart Citations
“…The derivatization results in potential disadvantages for GC analysis such as matrix interference, the time-consuming nature of the process, the need for an expensive derivatization reagent, and so on. In the last few years, LC-MS, especially LC tandem mass spectrometry (LC-MS/MS), has played an important role in AME detection without derivatization [10,11,12]. However, these methods need highly qualified technicians and can only be carried out in the lab.…”
Section: Introductionmentioning
confidence: 99%